2010
DOI: 10.1093/carcin/bgq037
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNA expression by budesonide, phenethyl isothiocyanate and cigarette smoke in mouse liver and lung

Abstract: Although microRNAs (miRNA) have extensively been investigated in cancer research, less attention has been paid to their regulation by carcinogens and/or protective factors in early stages of the carcinogenesis process. The present study was designed to evaluate the modulation of mRNA expression as related to exposure of neonatal mice to environmental cigarette smoke (ECS) and to treatment with chemopreventive agents. Exposure to ECS started immediately after birth and for 2 weeks after weaning. Thereafter, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 29 publications
5
75
0
Order By: Relevance
“…These findings, which support the interpretation that MCS is a strong promoting agent, are in line with our previous studies in mice exposed to MCS early in life, both in terms of molecular biomarkers (10)(11)(12)(13)(14)(15) and of tumors and other histopathological alterations (16)(17)(18)(19)(20)(21)(22). Clearly, all these studies have the limitation that the molecular analyses are done on whole tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings, which support the interpretation that MCS is a strong promoting agent, are in line with our previous studies in mice exposed to MCS early in life, both in terms of molecular biomarkers (10)(11)(12)(13)(14)(15) and of tumors and other histopathological alterations (16)(17)(18)(19)(20)(21)(22). Clearly, all these studies have the limitation that the molecular analyses are done on whole tissues.…”
Section: Discussionsupporting
confidence: 90%
“…We developed suitable models for evaluating the efficacy and tolerability of chemopreventive agents in mice exposed to MCS in terms either of molecular biomarkers (10)(11)(12)(13)(14)(15) and/or of lung tumors, both benign and malignant, and other histopathological alterations in multiple organs (16)(17)(18)(19)(20)(21)(22).…”
Section: Lapatinib or N-[3-chloro-4-[(3-fluorophenyl)methoxy]phenyl]mentioning
confidence: 99%
“…These miRNAs expressed differentially were the one associated with genes regulating stress response, protein repair, cell proliferation, and inflammation. No study on the effect of PEITC on miRNA expression in cancer has been reported so far (85).…”
Section: Phenethyl Isothiocyanatementioning
confidence: 99%
“…Environmental factors (EFs) have recently been utilized as new means of inferring the relationship between diseases and miRNAs. The miREnvironment database contains information of EFs, such as drugs [6], cigarettes [7], alcohol [8], viruses [9], stress [10], and radiation [11], which plays a significant role in affecting various diseases. By applying the propagation algorithm on the miRNA-miRNA similarity network, we found hidden potential to identify association between disease-miRNA.…”
Section: Introductionmentioning
confidence: 99%